Geoinformatics and hydrogeophysical-based delineation of groundwater potential zone through surface and subsurface indicators - Usman Basharat; Wenjing Zhang; Arshad Abbasi; Sehrish Mahroof; Abrar Niaz; Shoukat Husain Khan (Applied Water Science)
Abstract Groundwater is one of the world’s most essential and valuable natural resources, important to a country’s growth development; regions like Azad Kashmir, Pakistan, face unique challenges from rapid urbanization and climate variability, highlighting the need for detailed assessments of groundwater potential and recharge dynamics. The complexity of groundwater systems complicates the identification of potential and recharge zones. This study focuses on these issues in the Bagh region, which has distinct hydrogeological characteristics and a critical need for sustainable groundwater management. This study used geomatics and hydrogeophysical technologies to delineate the groundwater potential zone in the study area. This multidisciplinary method improves the precision and reliability of groundwater potential zone mapping. Groundwater potential zones were delineated by integrating the thematic layers created from the digital elevation model, sentinel 2, geophysical investigations, pre-existing maps, and field survey data into a GIS context. Different parameters were determined, reclassified, and standardized to shared ranges with weights. These parameters included rainfall, geology, slope, lineament density, drainage density, aspect, Topographic wetness index, Normalized difference vegetation index, Normalized difference water index, elevation, slope aquifer resistivity, and lithology. The analytical hierarchy process evaluation method developed the groundwater potential zonation map. The index was divided into three zones: High (33%) are located in areas with favorable conditions such as high rainfall, low slope, and permeable lithology, making them ideal for groundwater extraction; moderate (46%) have intermediate conditions; and low (21%) are characterized by steep slopes, low rainfall, and less permeable lithology, indicating limited groundwater availability. The generated map was validated using data from 30 existing water wells and springs and 50 geophysical data points derived from vertical electrical sounding. The validation results demonstrated moderate to good agreement with the evidence obtained, as indicated by an area under curve value of 79.6%.